Immunogenicity and tolerability of a bivalent virus-like particle norovirus vaccine candidate in children from 6 months up to 4 years of age: A phase 2 randomized, double-blind trial - Pio López; Eduardo López-Medina; Xavier Sáez-Llorens; Rodrigo deAntonio; Taisei Masuda; Paul M. Mendelman; James Sherwood; Frank Baehner; Astrid Borkowski (Taylor & Francis Group, 2023)
We conducted a dose-finding phase 2 study of the HilleVax bivalent virus-like particle (VLP) vaccine candidate (HIL-214) in two cohorts of children, 6-≤12 months and 1-≤4 years of age (N = 120 per cohort), in Panama and Colombia (ClinicalTrials.gov, identifier NCT02153112). On Day 1, children randomized to one of the four equal groups received intramuscular injections of four different HIL-214 formulations containing 15/15, 15/50, 50/50, or 50/150 μg of GI.1/GII.4c genotype VLPs and 0.5 mg Al(OH)3. On Day 29, half the children in each group received a second vaccination (N = 60), while the other half received saline placebo injections to maintain the blind. VLP-specific ELISA Pan-Ig and histo-blood group binding antigen-blocking antibodies (HBGA) were measured on Days 1, 29, 57 and 210. On Day 29, after one dose, there were large Pan-Ig and HBGA responses in both age cohorts with some indication of dose-dependence, and higher geometric mean titers (GMT) in the older children. A further increase in titers was observed 28 days after a second dose in the 6-≤12-month-old groups, but less so in the 1-≤4-year-old groups; GMTs at Day 57 were broadly similar across doses and in both age groups. GMTs of Pan-Ig and HBGA persisted above baseline up to Day 210. All formulations were well tolerated with mostly mild-to-moderate transient solicited adverse events reported by parents/guardians, and no vaccine-related serious adverse events occurred. Further development of HIL-214 is warranted to protect the most susceptible young children against norovirus.